Burden of ovarian cancer in China from 1990 to 2030: A systematic analysis and comparison with the global level - Wang, Ying; Wang, Zhi; Zhang, Zihui; Wang, Haoyu; Peng, Jiaxin; Hong, Li (Frontiers in Public Health, 2023)
Estimating the burden trends and risk factors of ovarian cancer (OC) can help develop effective management and prevention measures. However, there is a lack of comprehensive analysis concerning the burden and risk factors of OC in China. Here, we extracted prevalence, incidence, mortality, disability-adjusted life years (DALYs), years of life lost (YLLs), and years lived with disability (YLDs) data from the Global Burden of Disease Study 2019 (GBD 2019) and characterized OC burden in China by year and age. OC epidemiological characteristics were interpreted by conducting Joinpoint and Bayesian age-period-cohort analysis. We also analyzed risk factors and predicted the OC burden from 2019 to 2030. In China, there were about 196000 cases, 45000 new cases and 29000 deaths owing to OC in 2019. The age-standardized rates (ASRs) of prevalence, incidence and mortality have increased by 105.98%, 79.19% and 58.93% respectively by 1990. In the next decade, OC burden in China will continue to rise with a higher rate than the global level. The OC burden in people under 20 years of age is slowing down, while the burden in people over 40 years of age is getting more severe, especially in postmenopausal and older women. High fasting plasma glucose is the major factor contributing the most to OC burden in China, and high body-mass index has surpassed occupational exposure to asbestos to be the second risk factor. OC burden from 2016 to 2019 in China has increased faster than ever before, indicates an urgent need to develop effective interventions.